Pengaruh Pengalaman Wisatawan Terhadap Kepuasan Dan Niat Berkunjung Kembali : Study Pada Pengunjung Kebun Pak Budi Pasuruan - M Falih Maulana Noto Prasojo (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This research was conducted to determine "The Influence of Tourist Experience on Satisfaction and Intention to Return (Study on Visitors to Pak Budi Pasuruan's Garden)" The strategy used in this study was associative research with a quantitative approach, by distributing questionnaires as a data collection technique. The sampling method uses purposive sampling, which is a sampling technique where the people selected as samples are in accordance with the purpose of conducting research, the sample used is 100 respondents, carried out at Pak Budi Pasuruan's Garden Tour, and uses samples with the Lemeshow formula and uses data processing modeling using Smartpls 4.0 (Partial Least Square). The results of the study state that the variable Tourist Experience has a positive and significant effect on Tourist Satisfaction and Revisit Intentions.